PENGARUH TAX KNOWLEDGE DAN ATTITUDE RASIONALITY TERHADAP KEPATUHAN WAJIB PAJAK DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERATING - Anwar, Mila Karmila; Bulutoding, Lince; Anwar, Puspita Hardianti (ISAFIR: Islamic Accounting and Finance Review, 2022)
This study aims to examine the effect of tax knowledge and attitude rationality on taxpayer compliance with religiosity as a moderating variable at the Bulukumba Tax Service Office (KPP). This research is a quantitative research with a descriptive research approach. This study uses the theory of planned behavior (TPB) and attribution theory. The sample in this study amounted to 100 taxpayers registered at KPP Pratama Bulukumba. Determination of research samples based on purposive sampling method. Research data is primary data collected through direct questionnaire surveys. Data analysis used multiple linear regression analysis to determine the effect of tax knowledge and attitude rationality on taxpayer compliance. Moderating regression analysis with the absolute residual approach test the absolute difference value test. The results showed that tax knowledge and attitude rationality had a positive and significant effect on taxpayer compliance. In addition, the results of this study also show that religiosity moderates the relationship between tax knowledge on taxpayer compliance and religiosity cannot moderate the significant effect of attitude rationality on taxpayer compliance.